ETHICS OF POLITICAL LEADERSHIP IN THE ADMINISTRATION OF THE INDONESIAN GOVERNMENT - Tarigan, Grace Agustiani Br (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
It iis iexpected ithat istrengthening iethical ivalues iand imoral istandards ican isignificantly ireduce ithe iprevalence iof icorruption iin iIndonesia. iIn iaddition, ibureaucratic ireform iis iconsidered ia icrucial istep iin isupporting ianti-corruption iefforts iand iin iestablishing ia itransparent iand iefficient isystem iof igovernance. iThe irole iof iethics iin ipolitical ilife iand ipublic iadministration iis iseen ias iessential ito ithe isuccess iof ithese ireforms. This ipaper iexplores ithe iinterrelation ibetween iethics, imoral ivalues, iand icorruption icases iin iIndonesia, iwith iparticular iemphasis ion ithe iimportance iof iintegrity iand istrong imoral icharacter iin ileadership. iThe istudy iemploys ia iliterature ireview iapproach, idrawing icomparisons ifrom iprevious iresearch ithat ishares isimilar icultural ivalues iand isocial iperspectives. The ifindings ireveal ithat imany icorruption icases iin iIndonesia iare iclosely ilinked ito ithe iabsence iof iethical ileadership. iWhile icorrupt ipractices imay iarise ifrom ivarious icontributing ifactors, ithis iresearch ihighlights ithe isignificant irole iof iethics iand imorality iin ishaping icorrupt ibehavior iamong inational ielites.